Mycotic isolates from the uterus of endometritic cows and buffaloes in Himachal Pradesh - SHARMA, SHWETA; SINGH, MADHUMEET; VASISHTA, N K; SHARMA, N S (The Indian Journal of Animal Sciences, 2011)
Cows (238) and buffaloes (54) having turbid uterine discharge at estrus and had failed to conceive despite 3 or more attempts of artificial inseminations and/or natural services, were selected for this study. A wide assemblage of fungi could be incrilninated in endometritis samples. The overall incidence of fungal endometritis in cows was 15.5%. The noteworthy mycotic isolates were of the genera Cladosporiunl, Verticillium, Chr.ysosporium, MUC01 Alternaria, Cephalosporiuln, Aspergillus, Rhizopus, Rhodotorula, Mortirella, Candida and Geotrichum. Â